2011
DOI: 10.1007/s00011-011-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampal fimbria of cuprizone-treated animals as a structure for studying neuroprotection in multiple sclerosis

Abstract: Objective and designIt has been demonstrated that changes in the normal-appearing white matter (NAWM) in multiple sclerosis precede the appearance of classical lesions. The understanding of NAWM biology in an established disease model might help to clarify why some of them progress to active demyelinating lesions.Material or subjectsC57BL6 male mice (19–21 g) were used in this study.TreatmentDemyelination was induced by feeding mice a diet containing 0.2% cuprizone for up to 5 weeks.MethodsRoutine stainings (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(14 reference statements)
1
18
0
Order By: Relevance
“…The hippocampal white matter area Bfimbria region,^however, appeared to be resistant to the cuprizone intoxication. Comparable results were previously reported by our group (Kipp et al 2011;Norkute et al 2009). Furthermore, the partial (i.e., lateral part) vulnerability of the caudo-putamen has been reported previously by independent groups (Pott et al 2009;Xiao et al 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The hippocampal white matter area Bfimbria region,^however, appeared to be resistant to the cuprizone intoxication. Comparable results were previously reported by our group (Kipp et al 2011;Norkute et al 2009). Furthermore, the partial (i.e., lateral part) vulnerability of the caudo-putamen has been reported previously by independent groups (Pott et al 2009;Xiao et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…We started our analysis of anatomical lesions with staging of anti-Iba1-stained sections, rather than evaluating the degree of myelin loss in, for example, anti-PLP-processed slices. The reason for following this strategy was results from other studies, which indicated that microgliosis is a sensitive indicator for brain pathology, especially in humans and rodents (Kipp et al 2011;van der Valk and Amor 2009). Applying this order of looking at events in the cuprizone model, we were able to demonstrate that the lateral olfactory tract is vulnerable (i.e., displays significant microgliosis), whereas pathology is less obvious in the anti-PLP-stained section (compare Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The procedures were approved by the Review Board for the Care of Animal Subjects of the district government (Nordrhein-Westfalen, Germany) and performed according to international guidelines on the use of laboratory mice. Demyelination was induced by feeding 8-wk-old (19-21 g) mice a diet containing 0.2% cuprizone (bis-cyclohexanone oxaldihydrazone; SigmaAldrich) in ground standard rodent chow for the indicated period (31,33). Control mice were fed standard rodent chow.…”
Section: /J) Cxcl10mentioning
confidence: 99%
“…Evaluation of apoptosis on H&E stains was performed using welldefined morphological criteria, such as condensed and fragmented cell nuclei (33,39). Myelination of the CC was evaluated by two independent and blinded researchers in two different regions (area 225 and 265, according to the mouse brain atlas by Sidman et al) on a scale from 0 (complete demyelination) to 10 (normal myelination).…”
Section: Ihc and Evaluationmentioning
confidence: 99%